ETIMOLOGI SUFIKS ASING DALAM BAHASA INDONESIA PADA RUBRIK ZOOM OUT DALAM KORAN TEMPO - Maguna Eliastuti; Sangaji Niken Hapsari (Pujangga: Jurnal Bahasa dan Sastra, 2016)
ABSTRACT This study aims to determine concrete data about the etymology of suffixes foreigners in Indonesian on arubric Zoom Out in the newspaper tempo, to determine concrete data about the meaning resulting from theprocess etymology suffixes foreign Indonesian language and to determine concrete data regarding the changeof speech resulting from the process etymology foreign suffixes in Indonesian.Methods used to determine theetymology of suffixes foreigners in Indonesian on the rubric Zoom Out in Koran Tempo is by usingdescriptive method with pedekatan qualitative emphasize on content analysis, qualitative approach which isbased on the level of morphology relating to the issue said that experienced the process affix particleformIndonesian foreign suffix.After the authors analyzed the etymology of suffixes foreigners in Indonesian on therubric Zoom Out in Koran Tempo, the author can draw the conclusion that the use of words using the suffixforeigners in Indonesian as many as 166 words, suffixes foreigners in Indonesian form a noun or adjective,either which comes from the verb, noun or adjective. And the meaning resulting from the Indonesian foreignsuffixes can be either lexical or grammatical meaning. Key words: etymology foreign suffixes, rubric Zoom Out, koran Tempo